Microparticle Release During Normal Cesarean Delivery. (March 2018) - Hofer, Jennifer E.; Scavone, Barbara M.
Abstract : Coagulation increases during pregnancy and peaks during parturition. We hypothesized that an increase in microparticle (MP) levels in plasma occurs around the time of placental separation and subsides over several hours. We performed a prospective observational pilot study to investigate plasma MP levels in healthy parturients immediately before and after cesarean delivery. The primary outcome was MP levels at postdelivery time points compared to baseline levels. Samples underwent flow cytometry and staining to determine MP levels. Placental-derived MPs were further characterized for the presence of procoagulant proteins. Placental-derived MPs increased immediately after delivery before returning to baseline in healthy parturients.